1997
DOI: 10.1128/jvi.71.4.2591-2599.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative mutants of human MxA protein: domains in the carboxy-terminal moiety are important for oligomerization and antiviral activity

Abstract: Human MxA protein is an interferon-induced 76-kDa GTPase that exhibits antiviral activity against several RNA viruses. Wild-type MxA accumulates in the cytoplasm of cells. TMxA, a modified form of wild-type MxA carrying a foreign nuclear localization signal, accumulates in the cell nucleus. Here we show that MxA protein is translocated into the nucleus together with TMxA when both proteins are expressed simultaneously in the same cell, demonstrating that MxA molecules form tight complexes in living cells. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 49 publications
(72 reference statements)
3
41
0
Order By: Relevance
“…Our immunofluorescence analysis demonstrated that upon IFN τ treatment oMx1 was distributed diffusely throughout the cytoplasm. Among other Mx proteins, human MxA, 41,42 rat Mx2 and Mx3 43 and canine Mx1 and Mx2 44 are also localized in the cytoplasm. Secondly, unconventionally secreted proteins lack a hydrophobic signal peptide 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Our immunofluorescence analysis demonstrated that upon IFN τ treatment oMx1 was distributed diffusely throughout the cytoplasm. Among other Mx proteins, human MxA, 41,42 rat Mx2 and Mx3 43 and canine Mx1 and Mx2 44 are also localized in the cytoplasm. Secondly, unconventionally secreted proteins lack a hydrophobic signal peptide 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A polyclonal rabbit antiserum (44) or the mAb M143 (45) directed against the human MxA protein, a polyclonal rabbit antiserum specific for the N protein of LACV (kindly provided by R. Raju, Meharry Medical College, Nashville, TN) and a mAb directed against the G1 glycoprotein of LACV (kindly provided by F. Gonzalez‐Scarano, University of Pennsylvania, Philadelphia, PA) were used for immunofluorescence, immunoelectron microscopy and Western blot analysis. A goat polyclonal anti‐Syntaxin17 antibody (smooth ER) was kindly provided by R.H. Scheller, Howard Hughes School, Stanford, CA (23).…”
Section: Methodsmentioning
confidence: 99%
“…The formation of oligomers is indispensable for both MxA and MxB to restrict their target viruses. While MxA depends on its GTPase activity for its antiviral function, the GTPase activity of MxB is required to inhibit human herpesviruses but not HIV-1 (6,8,(11)(12)(13)(14)(15)(16)(17)(18)(19). MxA is cytoplasmic, whereas MxB is seen more at the cytoplasmic face of the nuclear envelope.…”
mentioning
confidence: 99%